Farming of giant freshwater prawn (Macrobrachium rosenbergii) in Bagerhat, Bangladesh - Shirin Akter; Md. Mer Mosharraf Hossain; Sanjoy Banerjee Bappa; Bipul Kumar Dey; Md. Farid Uz Zaman (Journal of Fisheries, 2014)
The study was carried out to know the present status of Macrobrachium rosenbergii culture in Bagerhat district, Bangladesh from March 2012 to January 2013. Education levels  of farmers were found as illiterate (12.3%), primary (36.19%), secondary (20%), SSC (13.33%), HSC (12.38%) and graduate (5.71%). M. rosenbergii culture was the primary and secondary occupation of 80% and 20% farmers respectively. Average stocking density and production in extensive, improved extensive and semi-intensive culture were 9609, 11502 and 22847 per ha and 193, 284 and 488 kg/ha/year respectively; rearing period ranges from 6-10 months and survival rate varied from 55 to 60%. In improved extensive and semi-intensive culture 82.86% and 71.43% farmers applied farm-made feed instead of company feeds respectively and 11.43% and 37.14% farmers used both feeds. 91.43%, 80% and 68.57% respondents responded on normal to high mortality in extensive, improved extensive and semi-intensive culture respectively. Lack of finance and appropriate technology, scarcity of quality PL, diseases and inadequate extension work were major problems of prawn culture.